Directional leads applied to spinal cord stimulation: A computational modelling study - Zhen Wu; Nianshuang Wu; Penghao Wang; Cheng Zhang; Changzhe Wu; Xiaolin Huo; Guanghao Zhang (PLoS ONE, 2026)
Spinal cord stimulation (SCS) is widely used to treat various types of pain. Directional leads, which exhibit directional focusing properties, have been applied in deep brain stimulation. Their targeting capability holds potential for further enhancing clinical SCS protocols. However, the actual stimulation effects of directional leads remain unclear and require further investigation. This study employed a computational modelling approach to develop SCS simulation models and a multi-compartment cable model of sensory fibers. These models were used to simulate the stimulation effects of directional leads in the human spinal cord. According to the reciprocity theorem, the evoked compound action potential (ECAP) generated by activated nerve fibers at recording contacts was calculated. Compared to traditional percutaneous leads, directional leads produced higher electric field strength and activating function in the spinal cord under the same current intensity, thereby activating a greater number of nerve fibers. Furthermore, increasing the angle between contacts further enhanced the advantages of directional leads. When the directional lead was rotated, the stimulation direction deviated from directly facing the spinal cord, resulting in a decreased number of activated nerve fibers. Under identical stimulation conditions, ECAP amplitudes recorded at different directional contacts showed variation; however, these differences remained within 6%. This study demonstrated the directional focusing advantage of directional leads and compared ECAP outcomes under varying conditions. The findings provide a solid theoretical foundation for the clinical application of directional leads.